Plato. Menexenus: Introduction, translation and notes - Cerdas, Emerson (Revista Archai, 2020)
This paper aims to present not only a translation of Plato’s Menexenus into Portuguese but also cultural and historical notes, as well as explanatory ones concerning translation choices. It also contains a brief introduction to the dialogue.